Molecular phylogeny reveals new morphological and ecological insights into the Cyperus margaritaceus–niveus complex - Martin Xanthos; George Burton; Lisa Pokorny; Alice Merrall; Isabel Larridon (Plant Systematics and Evolution, 2026)
The Cyperus margaritaceus–niveus complex (Cyperaceae) is a group of nine C4 Cyperus species ( C. karlschumanii , C. kibweanus , C. ledermannii , C. margaritaceus , C. nduru, C. niveus var. leucocephalus , C. somaliensis , C. sphaerocephalus , and C. tisserantii ) from Sub-Saharan Africa and Madagascar united by the combination of a capitate inflorescence, white–yellow glumes and swollen bulb-like bases. Previous molecular studies hinted that this complex forms a natural group within the C4 Cyperus Clade, although not all taxa were included. In this study, we used the Angiosperms353 bait kit to generate sequence data for all taxa in the complex. The species complex was resolved as monophyletic, while inter-species relationships produced differing results. Cyperus sphaerocephalus , C. kibweanus , C. ledermannii , C. somaliensis , and C. tisserantii were resolved as monophyletic, while C. karlschumannii appears monophyletic except for a moderately resolved isolated lineage that is positioned elsewhere. Cyperus niveus var. leucoephalus was resolved as paraphyletic. Cyperus nduru was resolved as polyphyletic even after rechecking determinations of the specimens. The latter result appears to show correlation with habitat in which one clade comprises specimens associated with Miombo woodland and another clade that comprising specimens associated with bowal grassland. This ecological difference correlates with differences in underground organ morphology. Cyperus margaritaceus requires further study to delimit since a specimen identified as this species is found in an unusual position in the phylogeny, possibly representing a new species to science. Combining this phylogenomic dataset with previous studies on morphometrics demonstrates how such integrative and iterative taxonomic methods can be the optimal approach in resolving species complexes in species-rich genera such as Cyperus , especially in the rapid diversifying C4 Cyperus Clade.